Cardiac Output Monitoring Managing Intravenous Therapy (COMMIT) to Treat Emergency Department Patients with Sepsis. Issue 2 (August 2016) - Hou, Peter C.; Filbin, Michael R.; Napoli, Anthony; Feldman, Joseph; Pang, Peter S.; Sankoff, Jeffrey; Lo, Bruce M.; Dickey-White, Howard; Birkhahn, Robert H.; Shapiro, Nathan I.
ABSTRACT: Objective: Fluid responsiveness is proposed as a physiology-based method to titrate fluid therapy based on preload dependence. The objectives of this study were to determine if a fluid responsiveness protocol would decrease progression of organ dysfunction, and a fluid responsiveness protocol would facilitate a more aggressive resuscitation. Methods: Prospective, 10-center, randomized interventional trial. Inclusion criteria: suspected sepsis and lactate 2.0 to 4.0 mmol/L. Exclusion criteria (abbreviated): systolic blood pressure more than 90 mmHg, and contraindication to aggressive fluid resuscitation. Intervention: fluid responsiveness protocol using Non-Invasive Cardiac Output Monitor (NICOM) to assess for fluid responsiveness (>10% increase in stroke volume in response to 5 mL/kg fluid bolus) with balance of a liter given in responsive patients. Control: standard clinical care. Outcomes: primary—change in Sepsis-related Organ Failure Assessment (SOFA) score at least 1 over 72 h; secondary—fluids administered. Trial was initially powered at 600 patients, but stopped early due to a change in sponsor's funding priorities. Results: Sixty-four patients were enrolled with 32 in the treatment arm. There were no significant differences between arms in age, comorbidities, baseline vital signs, or SOFA scores ( P > 0.05 for all). Comparing treatment versus Standard of Care—there was no difference in proportion of increase in SOFA score of at least 1 point (30% vs. 33%) (note bene underpowered, P = 1.0) or mean preprotocol fluids 1, 050 mL (95% confidence interval [CI]: 786–1, 314) vs. 1, 031 mL (95% CI: 741–1, 325) ( P = 0.93); however, treatment patients received more fluids during the protocol (2, 633 mL [95% CI: 2, 264–3, 001] vs. 1, 002 mL [95% CI: 707–1, 298]) ( P < 0.001). Conclusions: In this study of a "preshock" population, there was no change in progression of organ dysfunction with a fluid responsiveness protocol. A noninvasive fluid responsiveness protocol did facilitate delivery of an increased volume of fluid. Additional properly powered and enrolled outcomes studies are needed.